2023
DOI: 10.1177/17562864221150314
|View full text |Cite
|
Sign up to set email alerts
|

Immunoadsorption as maintenance therapy for refractory neuromyelitis optica spectrum disorder

Abstract: Background: Neuromyelitis optica spectrum disorder (NMOSD) is a rare relapsing autoimmune disease of the central nervous system, affecting mainly optic nerves and spinal cord. NMOSD pathophysiology is associated with anti-aquaporin-4 (AQP4) immunoglobulin G (IgG) autoantibodies. Rapid extracorporeal elimination of autoantibodies with apheresis techniques, such as immunoadsorption (IA), was proven to be an effective treatment of NMOSD attacks. Data on the long-term use of IA to prevent attacks or progression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Finally, intermittent PE or IA combined with or without concomitant immunosuppressive therapy has also been shown to prevent attacks in severe NMOSD in individual case reports [ 79 , 116 , 153 ].…”
Section: Treatment Of Nmosd: General Aspects and Outcome Measuresmentioning
confidence: 99%
“…Finally, intermittent PE or IA combined with or without concomitant immunosuppressive therapy has also been shown to prevent attacks in severe NMOSD in individual case reports [ 79 , 116 , 153 ].…”
Section: Treatment Of Nmosd: General Aspects and Outcome Measuresmentioning
confidence: 99%
“…Optimal and effective treatment during the acute phase of NMOSD is crucial for long-term benefits, as failure to fully recover from acute attacks can exacerbate disabilities. IA therapy can improve symptoms of acute spinal cord injury and vision impairment, and in some cases, can even attenuate neurological symptoms after reaching a stable phase ( 32 ). Consistent with past research, our patient demonstrated significant clinical symptom remission following IA therapy, with noticeable improvements in imaging and laboratory tests.…”
Section: Discussionmentioning
confidence: 99%